HBF4/ACN: A simple and efficient protocol for the synthesis of pyrazoles under ambient reaction conditions. Issue 3 (1st February 2020) - Hazarika, Roktopol; Konwar, Manashjyoti; Damarla, Krishnaiah; Kumar, Arvind; Sarma, Diganta
Abstract: An efficient and novel protocol for pyrazole synthesis has been developed by using fluoroboric acid as the acid catalyst. Simple and easily available 1, 3-diketone and hydrazine derivatives are taken as the substrates for this purpose. The reaction entails mild reaction conditions and produces desired pyrazoles in good to excellent yields. Easy accessibility, easy handling, broad substrate scope, evading metal catalyst and economic viability make this protocol advantageous to most of the previously reported literature. GRAPHICAL ABSTRACT: